Clinical Pharmacogenetics Implementation Consortium (CPIC) Guidelines for CYP2C19 and Voriconazole Therapy. Issue 1 (18th April 2017) - Moriyama, B; Obeng, A Owusu; Barbarino, J; Penzak, SR; Henning, SA; Scott, SA; Agúndez, JAG; Wingard, JR; McLeod, HL; Klein, TE; Cross, SJ; Caudle, KE; et al.
Abstract : Voriconazole, a triazole antifungal agent, demonstrates wide interpatient variability in serum concentrations, due in part to variant CYP2C19 alleles. Individuals who are CYP2C19 ultrarapid metabolizers have decreased trough voriconazole concentrations, delaying achievement of target blood concentrations; whereas poor metabolizers have increased trough concentrations and are at increased risk of adverse drug events. We summarize evidence from the literature supporting this association and provide therapeutic recommendations for the use of voriconazole for treatment based on CYP2C19 genotype (updates athttps://cpicpgx.org/guidelines/ andwww.pharmgkb.org ).